STREPTOMYCETE PLASMIDS CONTAINING BIOSYNTHESIS GENE CLUSTERS OF ANTITUMOR ANTIBIOTIC LIDAMICINSTREPTOMYCETE PLASMIDS CONTAINING BIOSYNTHESIS GENE CLUSTERS OF ANTITUMOR ANTIBIOTIC LIDAMICIN - L.V. Polishchuk (Biotechnologia Acta)
Anticancer antibiotic lidamycin is produced by Streptomyces globisporus C-1027 strain. The lidamycin biosynthesis cluster (LDM-cluster) is localized on its plasmid SGLP1.